2019
DOI: 10.5217/ir.2018.00113
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of care for inflammatory bowel disease

Abstract: Great strides have been achieved in the development of quality-of-care measures and standards for inflammatory bowel disease (IBD) over the last decade. The central structural component of care in IBD revolves around the multidisciplinary team, which should be equipped with the necessary resources to operate and implement decisions. Process measures have been defined by interest groups and can be adapted into process tools for the delivery of care for various patient subgroups and clinical scenarios. The emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
0
23
0
1
Order By: Relevance
“…There is growing international interest in quality improvement and benchmarking of IBD care within individual health care systems and between countries . The UK IBD Audit has served as a model for a recent national programme in Australia .…”
Section: Introductionmentioning
confidence: 99%
“…There is growing international interest in quality improvement and benchmarking of IBD care within individual health care systems and between countries . The UK IBD Audit has served as a model for a recent national programme in Australia .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Thus, risk assessment for viral hepatitis is one of the important quality process indicators for the management of IBD patients. 4 In addition, several areas of Asia, including Korea, show in-pISSN 1598-9100 • eISSN 2288-1956 https://doi.The treatment of inflammatory bowel disease (IBD) has been revolutionized for the last 10 years by the increasing use of immunomodulators and biologics. With immunosuppression of this kind, opportunistic infection is an important safety concern for patients with IBD.…”
mentioning
confidence: 99%
“…2,3 Thus, risk assessment for viral hepatitis is one of the important quality process indicators for the management of IBD patients. 4 In addition, several areas of Asia, including Korea, show in-pISSN 1598-9100 • eISSN 2288-1956 https://doi.…”
mentioning
confidence: 99%
“…Awareness of the quality of care is increasing [1,2]. The increased incidence of in ammatory bowel disease (IBD), including chronic in ammatory gastrointestinal-impaired ulcerative colitis (UC) and…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported on the quality of care in IBD patients [7][8][9][10]. To improve the quality of care of these patients, Donabedian's framework, which is composed of structure, process, and outcomes, can be used to set speci c and measurable goals [1,11]. Based on this framework, various quality indicators for IBD patients have been reported.…”
Section: Introductionmentioning
confidence: 99%